2024
DOI: 10.1186/s12916-024-03260-y
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness, implementation, and experiences of peer support approaches for mental health: a systematic umbrella review

Ruth E. Cooper,
Katherine R. K. Saunders,
Anna Greenburgh
et al.

Abstract: Background Peer support for mental health is recommended across international policy guidance and provision. Our systematic umbrella review summarises evidence on the effectiveness, implementation, and experiences of paid peer support approaches for mental health. Methods We searched MEDLINE, EMBASE, PsycINFO, The Campbell Collaboration, and The Cochrane Database of Systematic Reviews (2012–2022) for reviews of paid peer support interventions for m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 57 publications
(466 reference statements)
0
1
0
Order By: Relevance
“…In addition, many studies have shown that peer support plays an important protective role in the associations among life events, mental disorders, and addictive behavior. According to the stress-buffering model, the interaction between positive experience and peer support has the potential to counter the negative effects of stress [ 40 ], promote mental health [ 41 ], and reduce addictive behavior [ 42 ]. For instance, a longitudinal study conducted on 1301 middle school students emphasized that peer support may buffer the effect of family functioning on adolescent depressive symptoms [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many studies have shown that peer support plays an important protective role in the associations among life events, mental disorders, and addictive behavior. According to the stress-buffering model, the interaction between positive experience and peer support has the potential to counter the negative effects of stress [ 40 ], promote mental health [ 41 ], and reduce addictive behavior [ 42 ]. For instance, a longitudinal study conducted on 1301 middle school students emphasized that peer support may buffer the effect of family functioning on adolescent depressive symptoms [ 43 ].…”
Section: Introductionmentioning
confidence: 99%